ACADEMIC SUPERVISION: EFFORTS TO IMPROVE THE LEARNING PROCESS SKILLS OF ELEMENTARY SCHOOL TEACHERS - Farida Farida; Ary Kiswanto Kenedi (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
This research was motivated by findings regarding the learning process of elementary school teachers that were not in accordance with the characteristics of learning at schools. The findings revealed that teachers still used lesson plans which were only downloaded from the internet, the learning process and assessment carried out by teachers were still not in accordance with the demands of the curriculum. Therefore, an effort was needed to improve it. The purpose of this study was to determine the improvement of teacher skills in carrying out the learning process using a problem centered learning model through academic supervision activities. This research was a school action research by adapting the process of implementing from Mc Taggart and Kemmist's classroom action research. This research consisted of stages of planning, implementation, observation and reflection. This research activity was carried out at SDN 28 Rawang Timur, Padang involving 10 teachers. Based on the research conducted, it was found that the teacher got an average skill score of 88.86  in cycle 1 and got an average score of 83.59 in cycle 2. This concluded that there was an increase in teachers’ learning process skills through academic activities. This study suggested that it was necessary to agree on a schedule with the teacher so that the implementation of supervision could be carried out optimally. The implications of this research that it could be used as a basis by supervisors to improve the learning process skills of elementary school teachers.